El discurso político desde la publicidad de consumo en la televisión (2011)
This article analyzes the political dimension of the problem set in a globalized and postmodern context. From a critical standpoint, it always has been claimed that messages in the media contain an ideological discourse. Television, the great medium of our day, is no exception. Driven by the engine of advertising, the discourse of publicity is one of the major promoters of political imaginaries among the television audience. But, on what factors is the political discourse in television consumer advertising built? What is the relationship between the televised medium, advertising and the political discourse they promote?